Changes in rumen protozoal community by condensed tannin fractions of different molecular weights from a Leucaena leucocephala hybrid in vitro - Poothan Mookiah, Saminathan; Gan, Han Ming; Abdullah, Norhani; Wong, Clemente Michael Vui Ling; Ramiah, Suriya Kumari; Tan, Hui Yin; Sieo, Chin Chin; Ho, Yin Wan (The Society for Applied Microbiology, 2017)
Aims: To evaluate the effects of condensed tannins (CTs) fractions of differing molecular weights (MWs) from a Leucaena leucocephala hybrid-Rendang on the rumen protozoal community in vitro. Methods and Results: The effects of unfractionated CTs (F0) and CT fractions of different MWs (F1 > F2 > F3 > F4 > F5) on protozoal population and community were evaluated in vitro using rumen microbes and ground guinea grass as the substrate. Higher-MW CT fractions F1 and F2 significantly (P < 0·05) decrease the number of ciliate protozoa. The real-time PCR analysis showed that the total protozoa was significantly (P < 0·05) lower in F0 and all CTs with fractions F1 and F2 having the lowest value. High-throughput sequencing of the partial 18S rRNA gene showed that the genus Entodinium significantly (P < 0·05) decreased with increasing MWs of CT, whereas Anoplodinium-Diplodinium were significantly (P < 0·05) increased. Inclusion of the highest MW CT fraction F1 decreased the relative abundance of the minor genera such as Eudiplodinium and Polyplastron compared to the control and CT fractions F2–F5. Conclusion: CTs of differing MWs could reduce and alter the rumen protozoa population in vitro. This effect was more pronounced for higher-MW CTs. Significance and Impact of the Study: The high MW CTs should be considered as a feed supplement in the ruminant diet to reduce the protozoal population which are known to be associated with methanogens as a means to mitigate methane production in the rumen.